Positive Influence of Role Ambiguity on JD-R Motivational Process: The Moderating Effect of Performance Recognition - Martínez-Díaz, Ana; Mañas-Rodríguez, Miguel Ángel; Díaz-Fúnez, Pedro Antonio; Limbert, Caroline (Frontiers in Psychology, 2020)
Most previous research has shown the negative influence of role ambiguity on the employees' motivational process. This has led to the perception of role ambiguity as one of the main labor hindrance, with a negative influence on Job Demands Resources (JD-R) theory motivational process. Recent theories propose that job demands not only have a negative influence, they can also be perceived by employees as a challenge. However, there is little evidence of what elements of the organizational context facilitate this change. The objective of this study is to shed light on the possible effect of performance recognition by the team leader in the interpretation of role ambiguity as an obstacle or a challenge for employees. Data were obtained from 706 employees of a multinational company based in Almeria, Spain. Data confirmed the impact of performance recognition as a modulator of the negative effect of role ambiguity, causing a change in said influence. The inclusion of performance recognition transforms into positive the initial negative effect of role ambiguity in engagement and reduces the negative influence on extra-role behaviours.